KETERSEDIAAN RUANG TERBUKA HIJAU DALAM MENSUPLAI KEBUTUHAN OKSIGEN DI WILAYAH KABUPATEN MAGETAN TAHUN 2023 - Oktavia Putri Anggraini; Mujiyono; Handoyo; Hurip Jayadi; Amrita Yuli Astuti5 (Nusantara Hasana Journal, 2024)
As is the implementation of ATR/BPN Ministerial Regulation No. 14 of 2022 concerning the Provision and Utilization of Green Open Space which requires green open space to be 30% of the urban area. In 2023, Green Open Space in Magetan Regency will only be 12.5%, namely 2,025.6 Ha from 30%, namely 3,241.6 Ha mandated by the Ministerial Regulation. The type of research is descriptive. The results of the research show that, the results of the analysis of Green Open Space calculations based on Oxygen Needs in Magetan Regency in 2023, obtained a result of 5,846.48 Ha or 36.52%. If the existing available space is 2,025.6 Ha or 12.5%, then it is necessary to add Green Open Space based on oxygen requirements of 3,820.88 Ha or 24.02%. To overcome this shortage, it is necessary to add Green Open Space in the form of conservation and revitalization of existing natural open spaces to improve the quality of existing Green Open Spaces by local governments and the private sector as a commitment to environmental management in the form of allocation of regional land assets for Public and Private Green Open Spaces as well as empowering the community to participate. in increasing the quality and quantity of the importance of Green Open Space.